A new technique for the surgical repair of double cleft earlobe: modified Millard's rotation–advancement flap. Issue 3 (March 2015) - Eser, C.; Kerem, M.; Olguner, A.A.; Gencel, E.; Kesiktas, E.
Abstract The double cleft earlobe is a rare earlobe deformation. The most common causes of cleft earlobe are earring or piercing tear injuries and trauma. In this study, the cases of five patients (all women) attending the clinic between 2010 and 2013 suffering from a unilateral traumatic complete double earlobe cleft as a result of an earring injury were evaluated. The principles of Millard's cleft lip repair were applied during the repair of these double cleft earlobe deformities. This adaptation of Millard's technique to repair double earlobe clefts with a non-straight closure appears to give satisfactory results.